Carbon storage and ecological characteristics of restored and natural mixed deciduous forests in western Thailand - Chanlabut, Utain; Chankian, Jeeraporn; Hirun, Dussadeeporn; Auansrimueng, Wichuta; Nahok, Benchawan (Agriculture and Natural Resources, 2024)
Importance of the work: Assessment of carbon storage and ecological characteristics in mixed deciduous forests is crucial for understanding its succession and mitigating global warming. Objectives: This study examine carbon storage and ecological characteristics between mining-disturbed and undisturbed mixed deciduous forests in Ratchaburi, western Thailand. Materials & Methods: 2022, twelve 20 × 20 m plots were established in natural and restored mixed deciduous forests in Ratchaburi Province, Thailand. Trees with DBH ≥ 4.5 cm were inventoried. Ecological parameters (density, basal area, IVI, diversity) and forest carbon stocks (aboveground biomass, soil carbon) were assessed. Results: A total of 658 trees, representing 67 species from 22 families, were identified. The composition differed between two forests, with a 48.06% similarity in species. The Shannon-Wiener diversity was 2.90 in the restored forest (RF) and 3.36 in the natural forest (NF). The basal area was 231.67 ± 71.15 m2/ha in the RF and 416.41 ± 261.59 m2/ha in the NF. Mean tree height was 10.51 ± 3.72 m in the RF and 13.97 ± 4.41 m in the NF. Tree density was 1,779.17 ± 729.97 trees/ha in the RF and 962.50 ± 147.27 trees/ha in the NF. The total carbon stock was higher in the NF (366.27 ± 76.51 MgC/ha) compared to the RF (194.14 ± 45.80 MgC/ha). Main finding: The restored forest showed lower carbon storage and ecological parameters, indicating long-term mining impacts. However, the restored forest still serves as a carbon reservoir, contributing to the reduction of atmospheric CO2 levels and preserving biodiversity after prolonged restoration.